Editorial: Understanding Walls on the Periphery: Street Art and Graffiti between Commodification, Dissent and Oblivion - Abram, Sandi; Ušić, Eric (Street Art & Urban Creativity, 2024)
“Street art represents the voice of the periphery” — Alexandra Henry at Ljubljana Street Art Festival, 2022 The notion of the periphery usually serves as a starting point for critically examining and problematizing the contemporary dynamics of capitalism, ranging from global inequality to extractivism. This concept, however, may be also extended beyond the field of political-economic analysis (Wallerstein 2004) to embrace other socio-cultural dimensions. As Bazzini and Puttilli (2008, p. 23) argue, the transformation of cities in postmodernity has led to the disintegration of the relationship between center and periphery, giving rise to multiple centers and multiple peripheries. Thus, these multiplying centers and peripheries are not only mere political, geographic, urbanistic tipologies—and we could add topologies—but encompass also fluid cultural and symbolic flows (ibid.; see Appadurai, 1996), making them dialogic and relational. If we are to understand peripheries relationally (cf. Massey, 1994), then at the level of the production of social space, we must highlight their dialogic, communicative, transversive power/capabilities, and the inscribed meanings that are transmitted across and through these multiple peripheries, multiple centers. One such vehicle is the artistic, artivistic and political practices within urban space encapsulated in the often contested notion of ‘street art’ and, by extension, ‘graffiti’.